DINAMIKA KELOMPOK TANI â€œKOMPASâ€ DI DESA KANONANG IV KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA (The Dynamics of â€œKompasâ€ Farming Group in Kanonang IV Village, Kawangkoan Barat District, Minahasa Regency) - Fernando Fandi Maliangkay; Celcius Talumingan; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to determine the dynamics of the Kompas farmer group in Kanonang IV Village, West Kawangkoan District. This research was carried out for 3 (three) months, from September to November 2021. The data used in this study consisted of primary data and secondary data. Primary data were obtained through direct observation in the field and interviews with respondents using a list of questions that had been compiled, while secondary data were obtained from related agencies.The results showed that the dynamics of the â€œKompasâ€ farmer group in Kanonang IV Village, West Kawangkoan District were in the less dynamic category. The lack of dynamics of the